2017
DOI: 10.21608/mnj.2017.150040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Guideline on Nurses' Knowledge Regarding Patients With Minimal Hepatic Encephalopathy

Abstract: Background: Minimal hepatic encephalopathy (MHE) is the mildest type of spectrum of hepatic encephalopathy(HE). Patients with MHE have no recognizable clinical side effects of HE, but have mild cognitive and psychomotor deficits .The prevalence of MHE is high in patients with cirrhosis of liver and varies between 30% and 84%. Aim of this study was to study the effect of educational guideline on nurses' knowledge regarding patients with minimal hepatic encephalopathy. materials and method: A Quasi experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
0
0
Order By: Relevance
“…The findings of this study showed that the participants demonstrated a good level of knowledge regarding the HE. These findings are consistent with the findings of other studies conducted on nurses 17 , 18 that demonstrated that the majority of nurses had good knowledge about liver and HE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study showed that the participants demonstrated a good level of knowledge regarding the HE. These findings are consistent with the findings of other studies conducted on nurses 17 , 18 that demonstrated that the majority of nurses had good knowledge about liver and HE.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study showed that the participants demonstrated a good level of knowledge regarding the HE. These findings are consistent 4724 with the findings of other studies conducted on nurses 17,18 that demonstrated that the majority of nurses had good knowledge about liver and HE. On the other hand, this is inconsistent with the study conducted by Sohal et al, 2021, who reported a gap in level of nurses' knowledge toward HE care.…”
Section: Discussionsupporting
confidence: 89%